Desain dan Uji Coba Media Animasi Berbasis Chemo-Edutainment pada Materi Sistem Periodik Unsur - Oksismi Putri, Lidia; Yasthophi, Arif (Jurnal Riset Pendidikan Kimia (JRPK), 2021)
This research is motivated by innovative and interesting instructional media availability in supporting Chemistry learning process. This research aimed at producing an instructional media in the form of Chemo-Edutainment based animation media on valid periodic system material in terms of material validity, media validity, practicality and students questinnaire responses.. It was R&D (Research and Development) with 4D model. The instruments of collecting the data were validity test questionnaire, practicality test questionnaire, and student response questionnaire. Chemo-Edutainment based animation media on Periodic System of the Elements lesson was tested, it was valid with 91.87% percentage (very valid) and practical with 97.32% percentage (very practical), and it got student good response with 92.5% percentage (very practical). Keywords: Media, Animation, Chemo-Edutainment, Periodic System of Elements